The Role of Teachers' Digital Literacy in the Quality of Learning in the Independent Curriculum Era - Eni Setyo Rahayu (PT. AVID MEDIA INDONESIA, 2026)
The development of digital technology has driven a paradigm shift in learning, requiring teachers to possess adequate digital literacy, particularly in the implementation of the Independent Curriculum, which emphasizes flexibility, differentiation, and student-centered learning. This study aims to analyze the role of teachers' digital literacy on the quality of learning in the Independent Curriculum era. The research approach used a qualitative method with a descriptive design to explore in-depth teachers' experiences, understandings, and practices in utilizing digital technology in the learning process. Research subjects were purposively selected from teachers who have implemented the Independent Curriculum. Data collection techniques included in-depth interviews, learning observations, and documentation studies, while data analysis was conducted through inductive thematic analysis. The results show that teachers' digital literacy plays a strategic role in improving the quality of the learning process through adaptive planning, interactive learning implementation, and continuous and authentic assessment. Digital literacy also encourages the transformation of teachers' roles as reflective and innovative learning facilitators. Challenges to strengthening digital literacy include competency gaps, limited access to technology, and individual teacher readiness. This research confirms that continuously strengthening teachers' digital literacy is a crucial prerequisite for achieving quality and relevant learning, in line with the demands of the Independent Curriculum.